Topological Amenability Is a Borel Property - Renault, Jean (Mathematica Scandinavica, 2015)
We establish that a $σ$-compact locally compact groupoid possessing a continuous Haar system is topologically amenable if and only if it is Borel amenable. We give some examples and applications.